Pelatihan Pembuatan Video Pembelajaran Untuk Guru MTs Di Tangerang Selatan - Rufman Akbar; Chaerul Anwar; Johannes Hamonangan Siregar (Jurnal Pengabdian kepada Masyarakat TEKNO (JAM-TEKNO), 2020)
This Community Service activity was carried out because of the lack of the teachers' ability to make their own learning videos. The ability to make their own learning videos is needed in this pandemic era, because students have to do distance learning. The training is conducted using a combination of online and offline methods. Participants are given hand-on training to create, edit, and upload the created learning videos. Training using common applications and can be obtained easily. The applications used are also applications that do not require high computer resources, so they can be done with only standard devices. For example; MS Power Point, Canva, and Movie Maker.